Numerical simulation of negative streamers in strong non-uniform electric fields in nitrogen. Effect of needle radius and applied voltage on streamer velocity - Manuilenko, O.V.; Golota, V.I. (Плазменно-пучковый разряд, газовый разряд и плазмохимия, 2013)
The results of numerical simulations of the propagation of a negative streamer in nitrogen in the uniform and strongly non-uniform electric fields are presented. It is shown that the propagation velocity of the streamer in a nonuniform electric field is always higher than its velocity in an uniform field at given voltages on electrodes. It is shown that as the needle radius decreases, the velocity of the streamer increases. The growth of streamer velocity, with decrease of the needle radius, is stopped when the needle curvature radius reaches a certain critical size. It is shown that in the region of the strong nonlinearity, when the streamer dynamics is determined by the charge of the streamer head, its velocity as a function of the longitudinal coordinate is independent of the needle radius. It is shown that the velocity of the streamer increases with growth of the applied voltage.